The Italian legal system : an introduction. - Livingston, Michael A.; Monateri, P. G. (Pier Giuseppe); Parisi, Francesco, 1962- (Stanford, California : Stanford Law Books, 2016)
'The Italian Legal System' is an important and stimulating resource for those with specific interest in Italy and those with a more general interest in comparative law and the globalisation process.
This edition previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 11, 2016).
Keywords: Law -- Italy; Law; Jurisprudence & general issues; Comparative law; Laws of specific jurisdictions & specific areas of law